Acceptability of a lay-delivered intervention for depression in senior centers. (4th March 2021) - Raue, Patrick J.; Dawson, Alexis; Hoeft, Theresa; Russo, Joan; Ferguson, Dian; Green, Lynda; Petersky, Claire; Kaplan, Cecily
Abstract: Objective: We examined: 1. depression rates among senior center clients; and 2. the acceptability of a lay-delivered intervention for depression ("Do More, Feel Better") from the perspective of key stakeholders prior to its implementation. Method: We conducted cross-sectional surveys at four Seattle-area senior centers of 140 clients, 124 volunteers, and 12 administrators and staff. Client measures included the Patient Health Questionnaire-9 (PHQ-9) to determine depression severity, and items assessing depression treatment preferences. Following description of "Do More, Feel Better" as a lay-delivered intervention focused on increasing participation in rewarding activities, we used quantitative and qualitative items to assess acceptability to: 1. clients participating in; 2. volunteers administering; and 3. administrators and staff supporting the intervention. Results: 25% of senior center clients (35/140) endorsed elevated depressive symptoms (PHQ-9 ≥ 10). 81% of clients (114/140) reported that they would consider participating in "Do More, Feel Better, " and 59% percent of volunteers (73/123) expressed interest in learning how to assist others using the intervention. Administrators and staff reported high comfort levels with proposed volunteer training procedures, and they identified funding and staffing considerations as challenges to sustaining the intervention. Conclusion: Findings indicate high depression rates among senior center clients and support the acceptability of lay-delivered behavioral interventions for depression from a variety of stakeholders. Further investigation of the feasibility, effectiveness, and implementation of "Do More, Feel Better" is warranted, particularly in the context of a lack of health care professionals available to meet the mental health needs of older adults.